Men as Fathers in Child Protection. Issue 4 (2nd October 2019) - Brandon, Marian; Philip, Georgia; Clifton, John
ABSTRACT: When child protection professionals struggle to engage fathers and father figures, assessments may not accurately reflect the combination of resource and risk factors men present for children they care for, potentially endangering children and excluding men. In a mixed methods study in England of fathers and their perspectives on involvement in the child protection system and with their children, fathers persisted as a presence in children's lives. Yet there was little intervention with men and expectations were low and gendered. The study positioned perceptions of fathers in the child protection system dynamically, in six ways, along a shifting continuum of risk or resource for the child. Encouragingly, most movement was towards positive change and better parenting, although some men became or remained peripheral or excluded. A model is presented to foster earlier change and better interaction between men and social workers. Effective child protection work with men can come with empathic relationship building and more routine direct contact. IMPLICATIONS: Engaging fathers should be part of everyday practice in the child protection system and not an unmanageable task. Most men in the child protection system pose both a risk and a resource for their child. The actual and potential benefits they bring to their child should be discerned as well as any risks. When there is substantiated maltreatment it is crucially important that the children's fathers and father figures have been fully assessed.